Strengthening STEM education through a professional development program on enhancing teachers' TPACK in selected calculus topics - Malusay, Jeneveb T.; Cortes, Sylvester T.; Ontolan, Jay M.; Englis, Tess P.; Pagaran, Gabriel M.; Dizon, Rhey L. (Frontiers in Education, 2025)
One means to strengthen STEM education is providing appropriate and timely professional development programs among teachers. Hence, this study aimed to develop, implement, and evaluate a professional development (PD) program using training as the PD model on enhancing senior high school mathematics teachers' technological, pedagogical, and content knowledge (TPACK) on selected Calculus topics, namely, derivatives, integration, and their applications. The PD program consisted of a series of lectures and workshops in designing teaching–learning sequence of the topics. Employing the mixed-methods sequential explanatory design, initial and final TPACK of the 11 senior high school mathematics teachers were evaluated. Data analysis showed that teachers' TPACK progressed from generally limited to the expert level. At the end of the PD program, teachers were tasked to present a teaching learning sequence (TLS) as the output of the PD program and as evidence of their learning. These were rated by experts, and the results generally fall at the very satisfactory levels across all domains of TPACK. Supported by the teacher-participants' narratives, the PD program proved to be a transformative experience for teachers, thus enabling them to acquire technological, pedagogical, and content knowledge in derivatives, integration, and their applications.